2015
DOI: 10.1097/mog.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

Role of type 2 immunity in intestinal inflammation

Abstract: Purpose of Review Type 2 (Th2) immune responses play important roles in intestinal immunity by contributing to the maintenance of mucosal homeostasis, conferring protection against helminthic inflection, but also participating in pro-inflammatory pathways in chronic intestinal inflammatory disorders, including inflammatory bowel disease (IBD). The current review focuses on recent developments regarding the role of type 2 responses in intestinal inflammation. Recent Findings Th2 gut mucosal responses are prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 40 publications
1
38
0
1
Order By: Relevance
“…Understanding the mechanism of proinflammatory cytokines expressions is crucial to the development of therapeutic drugs for UC. Studies revealed that proinflammatory cytokines such as IL‐1β, IL‐6, TNF‐α, and IL‐17 are key mediators and initiators in the inflammation of colon in UC (Bamias & Cominelli, ; Catana et al, ; Chen & Sundrud, ; Fantini & Pallone, ). And transcriptions of these proinflammatory cytokines are dependent on the activation of NF‐κB pathway (Atreya, Atreya, & Neurath, ; Merga et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanism of proinflammatory cytokines expressions is crucial to the development of therapeutic drugs for UC. Studies revealed that proinflammatory cytokines such as IL‐1β, IL‐6, TNF‐α, and IL‐17 are key mediators and initiators in the inflammation of colon in UC (Bamias & Cominelli, ; Catana et al, ; Chen & Sundrud, ; Fantini & Pallone, ). And transcriptions of these proinflammatory cytokines are dependent on the activation of NF‐κB pathway (Atreya, Atreya, & Neurath, ; Merga et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond that, type 2 immune response is also involved in the process of wound healing in the gut (32, 33). Nevertheless, dysregulated and overreactive Th2 immunity may lead to detrimental inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…ILC2 are phenotypically demarcated from other lymphoid cells by the absence of conventional lin markers (for B, T, myeloid, and erythroid cells), in combination with the expression of ICOS, Sca-1, CD127, CD25, and receptors for IL-25 (IL17BR) and IL-33 (T1/ST2) by flow cytometry [33]. Following previous descriptions [24][25][26][27]33], lin 2 CD127 + ICOS + Sca-1 + cells, with an ability to produce IL-5 and IL-13, have been classified as ILC2. In adoptive-transfer experiments, ILC2 were sorted from pooled lamina propria mononuclear cells obtained from 25 burned mice and adjusted to 1 3 10 7 cells/ml in PBS.…”
Section: Isolation and Identification Of Ilc2mentioning
confidence: 99%
“…Type 2 cytokines (IL-4, IL-5, IL-9, IL-10, and IL-13), produced by type 2 cells (Th2 cells [19], M2Mf [20][21][22], and PMN-II [23]), play a role in the increased susceptibility of severely burned hosts to opportunistic infections. In addition, ILC2 have recently been described to be critical in the development of type 2 immune responses [24][25][26][27]. ILC2 are one of the family of ILCs consisting of 3 groups: ILC1 (NK cells and ILC1), ILC2, and ILC3 (natural cytotoxic receptor 2/+ ILC3 and lymphoid tissue inducer cells) [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation